Reparación integral: principios aplicables y modalidades de reparación - Glenda Granda Torres; Carmen del Cisne Herrera Abrahan (Universidad Hemisferios, 2020)
The objective of the present investigation is to analyze the integral repair, the principles on which it is based and the models of integral repair. The models of reparation can be applied in the same case, for this reason the evaluation of the damage caused is necessary to apply a specific type of reparation in which restitution, compensation, rehabilitation, satisfaction measures and guarantees of non-repetition may concur. The methodology used is the synthetic analytical method. The article consists of four sections. The first section develops the introduction of the research work. The second section analyzes comprehensive reparation, its access and consultation with victims of reparations, beneficiaries of reparations, adequate proportional reparations, causality; and, standard and burden of proof. The third section examines the principles on which reparations are based. In the fourth section the models of integral reparation are developed, among them the individual reparation that includes restitution, monetary compensation and rehabilitation; and, in the collective reparation, measures of satisfaction and guarantees of non-repetition are studied and it is concluded that comprehensive reparation is a right of the victims recognized in international law, therefore several principles applicable at the time of issuing reparation are recognized. In addition, there are two ways to fully repair the victim, one that is individual and the other that is collective.